The Role of Endoscopic Assistance in Surgery for Pediatric Cholesteatoma in Reducing Residual and Recurrent Disease - Nader Nassif; Luca Oscar Redaelli de Zinis (MDPI AG, 2024)
The primary aim of this study was to evaluate long-term recurrent and residual disease after surgery for acquired cholesteatoma in children according to surgical approach. A total of 71 interventions performed on 67 pediatric patients were included in the study. Canal wall-up tympanomastoidectomy (CWUT) was performed in 31 ears (13 with endoscopic assistance), a transcanal esclusive endoscopic approach (TEEA) was used in 22, and canal wall-down tympanomastoidectomy (CWDT) was performed in 18. Overall, the cholesteatoma relapse rate estimated by the Kaplan-Meier method was 47 ± 6% at 12 years; the recurrent cholesteatoma rate was 28 ± 6% and the residual cholesteatoma rate was 26 ± 5%. The relapse rate according to surgical approach was 33 ± 11% for CWDT, 60 ± 9% for CWUT, and 40 ± 11% for TEEA (p = 0.04). The difference for recurrent disease was no recurrent disease for CWDT, 42 ± 9% for CWUT, and 32 ± 11% for TEEA (p = 0.01). The residual disease rate was significantly reduced with endoscopy: 42 ± 8% without endoscopy vs. 9 ± 5% with (p = 0.003). CWDT can still be considered in primary surgery in case of extensive cholesteatomas and small mastoid with poor pneumatization. TEEA can be recommended for small cholesteatoma not extending to the mastoid to reduce morbidity. Endoscopic assistance seems useful to reduce residual disease in CWUT, whereas it does not have a significant impact on preventing recurrent disease.